Dancing in a Red Dress: Empowering Metaphors of Academics’ Experiences of the Manuscript Peer Review Process - Hammond, Kay; Trafford, Julie (Informa UK Limited, 2023)
The peer review of journal article manuscripts is a complex and emotionally fraught process. This article draws on how 25 academic authors used metaphor to describe their experiences of manuscript peer review. A critical analysis of these metaphors provided insight into the structures, relationships of power, and their emotional impacts. Over their careers, some academics reconceptualised their metaphors more powerfully to describe their evolving experiences and confidence over time. Their metaphors repositioned their sense of power within the reviewer/reviewee binary. We discuss how these reconceptualisations could guide new authors to manage feelings, thinking, and actions during peer review. This research makes an original contribution by extending the exploration of how metaphors and their reconceptualisations build emotional resilience. Academics new to publishing may gain a greater sense of empowerment while navigating the peer review process, reduce the negative emotional impacts, and prevent the resulting loss of valuable research.
Keywords: 13 Education; 39 Education